Pandangan Hukum Islam terhadap Euthanasia atau Bantuan Bunuh Diri dalam Kasus Penyakit Terminal - Rozzak Nawwir Qolby; Sitti Shaquila Dzakirah; Alya Putri Babelinda (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
This study aims to explore Islamic legal views on euthanasia, particularly in the context of terminally ill patients. Using a literature study approach, this study analyzes Quranic verses, hadiths, and the views of scholars on euthanasia, which is generally rejected in Islamic law. As an alternative, palliative care is identified as a more appropriate ethical solution, focusing on alleviating pain and improving the patient's quality of life. This study also underlines the importance of dialogue between health professionals and scholars to develop care protocols that comply with sharia principles. These findings suggest the need for better education and training for health professionals on medical ethics in the context of Islamic law. In doing so, it is hoped that health practices can better respect religious values ​​and meet patient needs more effectively.